AN ANALYSIS OF STUDENTS’ WRITING PROBLEMS IN ANALYTICAL EXPOSITION TEXT - Kulsum, Eva Meidi; Khodijah, Neng Siti (JURNAL EDUCATION AND DEVELOPMENT, 2025)
Mastering writing skills is very important in learning English because writing is a productive skill that allows students to express ideas, thoughts and information in a structured and clear way. In practice, many students experience various difficulties moreover when they have to write an analytical exposition text. This study tried to seek a deep understanding related to the phenomenon of problems faced by students in writing analytical exposition text. This research employed qualitative descriptive method by distributing questionnaire (20 items). 33 students from one of Senior High Schools in Bandung, participated as the object of this study. They were selected using purposive sampling technique. Based on the result of the questionnaire, there are five components of writing namely: Organization, Vocabulary, Grammar, Mechanics, and Content. Majority of students (65%) experience problems in organization, shown by mean score of 2,5. On the other hands, there were more than 50% students experienced difficulty in vocabulary mastery. Besides, almost half of students, with mean score: 2,09, stated that they were confused about correct grammar. Then the majority of students (55%) answered that they had difficulty in mechanics including punctuation, spelling and capital letters. Lastly, most students (shown by the highest mean score) answered content provokes their problems in writing. However, it is necessary for educators to emphasize these areas in their lesson plans in overcoming students' writing challenges and improve their ability to produce an effective analytical exposition text.